Analysis of Service Quality Factors in the Grab Application on User Satisfaction using the Service Quality (SERVQUAL) Method - Yanto, Dimas Hadi; Indah, Dwi Rosa; Novianti, Hardini; Sanjaya, M. Rudi; Gumay, Naretha Kawadha Pasemah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The development of information technology in the digital era has had a significant impact, including on online transportation services such as Grab. However, Grab users frequently complain about slow response times from customer support when handling complaints, as well as recurring issues with the balance feature, as reflected in complaints like